From Empowerment to Domesticity: The Case of Rosie the Riveter and the WWII Campaign - Santana, María Cristina (Frontiers in Sociology, 2016)
During WWII American women were asked to join in producing the “vital machinery of war” by working in factories building planes, by being nurses, and by being pilots among other jobs. Getting women to work in industries was a tremendous sales proposition as stated by Paul McNutt, the director of the War Manpower Commission in 1943. The war posters and magazine ads of the time reinforced the duty women had towards the war effort. Although women at the time were mostly occupying the private space, the war campaign of Rosie the Riveter inspired many of them to take their work to the public. This descriptive paper tried to answer the following two questions of inquiry: How did women’s employment during WWII become a temporary empowerment and what short and long-term changes in women’s lives were brought about by the war campaign of Rosie the Riveter. While the short-term changes brought women back to the private space and domesticity, some of the conclusions of the long-term changes in women’s lives dealt with variations in the workspace, salary, and military benefits. The influence of how empowered women felt following Rosie the Riveter is an inconclusive collection of the voices of those women during and after WWII.